2018
DOI: 10.1093/aobpla/ply036
|View full text |Cite
|
Sign up to set email alerts
|

Functional traits partially mediate the effects of chronic anthropogenic disturbance on the growth of a tropical tree

Abstract: Understanding how trees mediate the effects of chronic anthropogenic disturbance is fundamental to developing forest sustainable management strategies. The role that intraspecific functional diversity plays in such process is poorly understood. Several tree species are repeatedly defoliated at large scale by cattle breeders in Africa to feed livestock. In addition, these tree species are also debarked for medicinal purposes. These human-induced disturbances lead to biomass loss and subsequent decline in the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 76 publications
(119 reference statements)
0
12
0
1
Order By: Relevance
“…But species that have useful bark are also closely associated to NAs, giving credit to the idea that using bark on a regular basis is negatively impacting individual demographic performance (but see Amahowe et al. ). Conclusions are more difficult to draw for species belonging to the “medicine and magic” and “arts and crafts” categories, which showed no clear pattern.…”
Section: Discussionmentioning
confidence: 99%
“…But species that have useful bark are also closely associated to NAs, giving credit to the idea that using bark on a regular basis is negatively impacting individual demographic performance (but see Amahowe et al. ). Conclusions are more difficult to draw for species belonging to the “medicine and magic” and “arts and crafts” categories, which showed no clear pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the large number of traits that could impact plant fitness or performance, the functional trait research program typically focuses on a set of commonly and easily measured traits (e.g., Westoby 1998;Westoby et al 2002;Westoby and Wright 2006). It is thought that these traits represent fundamental tradeoff axes that indicate life history strategies, the abiotic and biotic interactions of individuals and species, and their overall fitness or performance given the abiotic and biotic contexts (Ackerly 2003;Swenson 2012;Adler et al 2014;Funk et al 2017;Amahowe et al 2018). To begin the review, we will focus on the most commonly measured functional traits (i.e., the wood economics spectrum, the leaf economics spectrum, and seed economics spectrum) and later in the text we will expand our discussion of functional diversity to include a larger variety of traits and functions.…”
Section: Introductionmentioning
confidence: 99%
“…The other end of the spectrum represents longer-lived, slower-growing trees with low SLA, nitrogen, and phosphorus (Wright et al 2004;Donovan et al 2011). Some work has shown that the wood economics spectrum is orthogonal to the leaf economics spectrum (Baraloto et al 2010;Dwyer and Laughlin 2017;Amahowe et al 2018). This contrasts with other work demonstrating a tight coordination between leaf and wood hydraulic traits (e.g., Santiago et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…africana is listed as a vulnerable tree species on the International Union for Conservation of Nature (IUCN) Red List (African Regional Workshop, ). In West Africa, much research effort has been invested in promoting the sustainable management and conservation of the species by assessing the local importance of its uses (Houehanou et al., ; Balima et al., ) and the variation of its population attributes in relation to climatic condition and anthropogenic disturbance (Nacoulma et al., ; Mensah et al., ; Amahowe et al., ). However, little is known of the population genetics of A. africana , as is the case for most endangered African tree species (Houehanou et al., ).…”
mentioning
confidence: 99%